1997
DOI: 10.1007/s002340050367
|View full text |Cite
|
Sign up to set email alerts
|

Angioarchitecture associated with haemorrhage in cerebral arteriovenous malformations: a prognostic statistical model

Abstract: The overall haemorrhagic risk of a cerebral arteriovenous malformation (cAVM) is 2-4% per year. However, the individual risk of haemorrhage has never been determined. This study was undertaken to assess the haemorrhage risk of an individual cAVM. Neuroangiographic findings of 160 cAVM were analysed retrospectively, looking at 30 angiographic features. A statistical model was established by logistic regression to evaluate the risk of an individual cAVM. We statistically correlated 15 parameters with the haemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(59 citation statements)
references
References 0 publications
3
51
1
4
Order By: Relevance
“…Studies have also shown that the presence of venous stenosis on angiography increases the rate of intracranial hemorrhage. 85,104 It is estimated that for unruptured AVMs, regardless of the other risk factors, the average annual rate of bleeding ranges from 2% to 4%. 13,107 Kondziolka et al 73 proposed the following formula taking into account the patient's age to estimate the lifetime risk of hemorrhage for an AVM: It is also estimated that the average annual case fatality rate is around 1% for AVMs.…”
Section: Natural Historymentioning
confidence: 99%
“…Studies have also shown that the presence of venous stenosis on angiography increases the rate of intracranial hemorrhage. 85,104 It is estimated that for unruptured AVMs, regardless of the other risk factors, the average annual rate of bleeding ranges from 2% to 4%. 13,107 Kondziolka et al 73 proposed the following formula taking into account the patient's age to estimate the lifetime risk of hemorrhage for an AVM: It is also estimated that the average annual case fatality rate is around 1% for AVMs.…”
Section: Natural Historymentioning
confidence: 99%
“…Likewise, venous ectasia/varix is defined as at least a doubling of the diameter of the draining vein. Venous ectasia is predicted to be associated with increased haemorrhagic risk [15]. Presence of angiogenesis (moya moya type phenomenon) also appears to increase the risk of haemorrhage associated with venous stenosis [13].…”
Section: S Chakraborty P Eldridge and H C Nahser E130mentioning
confidence: 99%
“…[6][7][8] Studies in adults have identified radiological features that are associated with haemorrhagic presentation and future haemorrhage. [9][10][11] Similar studies on AVM in children are, however, scarce and mostly based on studies from Europe and North America. 12,13 Whether those angiographic features that predict haemorrhage in Caucasian children with AVM similarly predict haemorrhage in Chinese children with AVM is unknown.…”
Section: Introductionmentioning
confidence: 99%